2021
DOI: 10.1186/s40246-021-00359-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective chromosome 1q32 haplotypes mitigate risk for age-related macular degeneration associated with the CFH-CFHR5 and ARMS2/HTRA1 loci

Abstract: Background Single-variant associations with age-related macular degeneration (AMD), one of the most prevalent causes of irreversible vision loss worldwide, have been studied extensively. However, because of a lack of refinement of these associations, there remains considerable ambiguity regarding what constitutes genetic risk and/or protection for this disease, and how genetic combinations affect this risk. In this study, we consider the two most common and strongly AMD-associated loci, the CFH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 82 publications
(151 reference statements)
0
29
0
Order By: Relevance
“…The consequences of genetic mutations driving AMD is for instance often detected late in life; however, their effect on retinal and choroidal structures is likely to begin much earlier. An effective way to address this is to stratify subjects base on genetic susceptibility for disease (Pappas et al, 2021) and to exclude those at high risk from cross-sectional and longitudinal analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of genetic mutations driving AMD is for instance often detected late in life; however, their effect on retinal and choroidal structures is likely to begin much earlier. An effective way to address this is to stratify subjects base on genetic susceptibility for disease (Pappas et al, 2021) and to exclude those at high risk from cross-sectional and longitudinal analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort was stratified into genetic groups using CFH-CFHR5 and ARMS2/HTRA1 diplotype combinations. Genetic groups were defined based on the risk-conferring variants rs1061170 ( CFH Y402H ) on Chr1 and rs10490924 ( ARMS2 A69S ) on Chr10 with the goal of isolating genetic AMD risk either at 1 of the loci or at both. Participants included in this study carried 2 risk alleles on Chr1 and no risk alleles on Chr10 (Chr1-risk group), 2 risk alleles on Chr10 without any risk alleles on Chr 1 (Chr10-risk group), or 2 risk alleles on both Chr 1 and Chr10 (Chr1&10-risk group) (eTable 1 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…We found that the deletion is largely out of phase with the CFH Y402H risk allele (D’=0.87) in AFR haplotypes; thus, it cannot fully explain the reduced effect size. Stratified by local ancestry, haplotypes in AA were analyzed using two models ( 38, 39 ), excluding SNPs that are rare in AFR haplotypes (Table S19) . While both models suggest that the putative risk haplotype may have a lower frequency in AFR compared to EUR, neither model demonstrated enrichment in cases with homozygous AFR local ancestry; they did, however, find haplotypes with enrichment in cases with homozygous EUR local ancestry.…”
Section: Resultsmentioning
confidence: 99%